PENINGKATAN KETERAMPILAN INSTALASI PERANGKAT KERAS KOMPUTER SEBAGAI SARANA PENINGKATAN KOMPETENSI SISWA SMK MAGANG - I Ketut Wiryajati; I Nyoman Wahyu Satiawan; Ida Bagus Fery Citarsa; Made Budi Suksmadana; Supriono; I Ketut Perdana Putra; Ida Ayu Sri Adnyani (Jurnal Pepadu, 2024)
In the rapidly developing digital era, technical skills in information and communication technology are very important for Vocational High School (SMK) students, especially those who are doing internships. Mastery of computer hardware, such as installation and maintenance, is a vital skill to compete in the world of work. Intensive training in computer hardware installation during internships aims to improve the competence of vocational high school students, making them better prepared to face industry demands.The training methods used include planning based on needs analysis, orientation, balanced implementation between theory and practice, and continuous evaluation. This training succeeded in improving students' practical and theoretical skills, with 85% of participants being able to complete installation tasks well. In addition, the average student score in the theory exam increased from 60% to 85%. As many as 80% of participants obtained competency certificates, which increased their competitiveness in the job market.In conclusion, this training is effective in improving the technical competence of vocational high school students in computer hardware installation, making them better prepared to enter the world of work.